Beyers Naude, Ekumeniese baanbreker in Suid-Afrika : 1960-1994 (Afrikaans) - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD (Science of Religion and Missiology))--University of Pretoria, 2005.